The Effect of Ownership Structure and Audit Quality in Producing High-Quality Financial Statements - Evidence from the Iraq Stock Exchange - Wahhab, Asaad Mohammed Ali; Khlaif, Murtadha Hasan (Technium Social Sciences Journal, 2022)
The research aims to measure the impact of the ownership structure and auditing quality in producing high-quality financial statements for a sample of commercial banks on the Iraqi Stock Exchange. Banks remain (23) banks; accordingly, (13) commercial banks were selected as a sample for the research. Their percentage was (57%) of the sample size, as the volume of traded shares, according to the reports of the Iraq Stock Exchange for the year 2020, amounted to (368,460,287497) shares, with a value of (193627218281). Pdt. To achieve the objectives of the research, the researcher used data for the research sample bank for the years (2011-2020), and the ownership structure of the company was measured through the following equation: Ownership structure = (number of shares owned by the company ÷ number of outstanding shares), while the quality of the audit was measured using a variable It is fictitious, where 1 is given to companies that have been audited by the four major auditing companies and 0 if the company is audited by other local companies, and the researcher will use the method of quantitative and statistical analysis together to reach the results and conclusions, and the most important conclusions reached by the research is that the structure of Ownership of major shareholders does not have a significant effect on the financial statements in the banks of the research sample, and the structure of administrative, family, governmental, foreign and exchange ownership does not have a positive moral effect on the financial statements in the banks of the research sample, while the structure of institutional Ownership and concentration of Ownership have a positive moral effect on the financial statements In the companies listed on the Iraq Stock Exchange, as for the quality of the audit, the results showed that there is a direct correlation between the application of the audit. The subscriber and the high-quality financial data and the results also showed that the financial data in the Iraqi banks in the research sample are appropriate, and this means that there is an impact on the accounting information (earnings per share, cash flow per share, book value per share) on the share price in the Iraqi stock market.